Representative volume element estimation for desorption isotherm of concrete with sliced samples. (October 2015) - Wu, Qier; Rougelot, Thomas; Burlion, Nicolas; Bourbon, Xavier
Abstract: The aim of this study is to determine the Representative Volume Element (RVE) size related to the desorption isotherm on concrete. Slices of three thicknesses taken from cast cylinders of an OPC concrete were desorbed from fully saturated condition to the dry state. The slice thickness had no clear influence on the water content once mass stabilization was reached. A method is being proposed to determine the RVE based on a statistical analysis of the water contents (or water saturation degrees) of the slices. The results show that a sample with the volume 7 d 3 may be considered as the RVE of an OPC concrete ( d is the maximum aggregate size).